Muscular imbalance and shoulder pain in volleyball attackers - Kugler, A.; Kruger-Franke, M; Reininger, S.; Trouillier, H. H.; Rosemeyer, B. (British Journal of Sports Medicine, 1996)
OBJECTIVE: In overhead sports such as volleyball, baseball, or tennis shoulder problems are very common. The aim of this study was to identify features which may correlate with shoulder problems in volleyball attackers. METHODS: 30 competitive volleyball attackers (mean age 25 years) were included in the study; 15 were suffering from shoulder pain and 15 had no history of shoulder pain. The results were compared with those of a control group of 15 recreational athletes without any overhead sports activities. RESULTS: Volleyball attackers have a different muscular and capsular pattern at the playing shoulder compared to the opposite shoulder. Their playing shoulder is depressed, the scapula lateralised, and the dorsal muscles and the posterior and inferior part of the shoulder capsule shortened. These differences were of more significance in volleyball attackers with shoulder pain than in volleyball players without shoulder pain. In contrast to recreational athletes without any overhead sports activity, there were no significant difference in the comparison of the two shoulders. The histories, clinical and sonographic findings did not reveal further typical features for volleyball attackers with shoulder pain. CONCLUSIONS: Muscular balance of the shoulder girdle is very important in this sport. It is therefore imperative to include adequate stretching and muscular training programme for the prevention, as well as for therapy, of shoulder pain in volleyball attackers.